Exploring Prospects of Monooxygenase-Based Biocatalysts in Xenobiotics - Dubey, K.K.; Kumar, P.; Singh, P.K.; Shukla, P.
Enzyme technology has progressed in recent years and the hunt for novel enzymes for industrial uses is a big challenge for many microbiologists. These enzymes can be used in a variety of applications provided they are efficient and are able to operate under industrial preference. This task is challenging and demanding and has not been fully covered by conventional microbiologists. The latest update on microbial monooxygenase-based biocatalysts in xenobiotics replicates its importance in hydrocarbon degradation but the work is limited with very few options of enzymes and its regioselectivity and enantioselectivity is reliant on overall recitation of such enzymes. Present chapter describes the key aspects of the overall research scenario regarding microbial monooxygenases which are currently used as a biocatalyst in xenobiotic applications. © 2014 Elsevier Inc. All rights reserved.
Keywords: BIOCATALYST; BIODEGRADATION; MONOOXYGENASES; REGIOSPECIFICITY; XENOBIOTICS